Improving Student Learning Outcomes Through The Use of Kahoot Media - Karliana Indrawari; Idi Warsah; Aini Syahira Jamaluddin (Fokus)
Abstract. The purpose of this research is to determine the application of kahoot media in the Islamic Education Methodology course at the Islamic Education Study Program, IAIN Curup; to determine student learning outcomes in the Islamic Education Methodology course after applying kahoot media in the Curup Islamic Education Study Program; and to determine the effectiveness of the application of kahoot media on student learning outcomes in the Islamic Education Methodology course at the Islamic Education Study Program.